Exploring the load-velocity profile with sprint swimming performance and sex differences - Ruiz-Navarro, J. J.; Born, D.-P.; Febles-Castro, A.; Gay, A.; López-Belmonte, Ó.; Morales-Ortíz, E.; López-Contreras, G.; Arellano, R. (International Journal of Sports Medicine, 2025)
This study aimed to investigate the relationship between the load-velocity profile and sprint swimming performance and kinematics, explore the inter-relationships of the load-velocity profile variables and blood lactate concentrations [La-] and dry-land strength (pull-ups), and examine sex-based differences. Twenty-seven swimmers (15 males: 19.2±3.7 y; 50 m front-crawl 550±70 World Aquatics points; 12 females: 17.7±2.4 y; 50 m front-crawl 552±63 World Aquatics points) underwent a 50 m front-crawl all-out swim test, a load-velocity profile test, and a pull-up test. Theoretical maximum velocity was associated with sprint swimming performance (r>0.863 and p<0.001), but not the theoretical maximum load (L 0) or the slope (p>0.05) for both sexes. An association between kinematics during the load-velocity profile test and free swimming was weakened as the load increased, with the correlation coefficient (r) decreasing from 0.929 to 0.403. Theoretical maximum velocity and theoretical maximum load were primarily associated with both sexes with the first (r>0.950 and p<0.001) and last (r>0.849 and p<0.001) semi-tethered trials, respectively. Only in females [La-] was associated with the theoretical maximum load and slope (r>0.573 and p<0.05). Males exhibited greater values than females in all the assessed variables (p<0.05) except for stroke rates and [La-]. The load-velocity profile is a valuable tool for assessing performance in both sexes. Kinematic parameters were related between semi-tethered and free swimming; however, association diminished with increasing load.